Parental age, genetic mutation, and cerebral palsy. Issue 1 (January 1993) - Fletcher, N A; Foley, J
Abstract : Parental age and birth order were studied in 251 patients with cerebral palsy. No parental age or birth order effects were observed in spastic quadriplegia or diplegia, but a paternal age effect was detected in those with athetoid/dystonic cerebral palsy and congenital hemiplegia. These observations indicate that some cases of athetoid/dystonic or hemiplegic cerebral palsy might arise by fresh dominant genetic mutation.